Molecular subtypes of osteosarcoma classified by cancer stem cell related genes define immunological cell infiltration and patient survival - Guo, Lei; Yan, Taiqiang; Guo, Wei; Niu, Jianfang; Wang, Wei; Ren, Tingting; Huang, Yi; Xu, Jiuhui; Wang, Boyang (Frontiers in Immunology, 2022)
Recent studies have shown that tumor stemness has biological significance in tumorigenicity and tumor progression. However, the potential roles of cancer stemness in tumor microenvironment (TME) cells infiltration in osteosarcoma remain unknown. Methods: In this study, we identified different cancer stem cell-associated subtypes in osteosarcoma based on 25 cancer stem cell-associated genes by consensus clustering analysis, and we comprehensively evaluated the association between these subtypes and immunocytes infiltration in the TME. The CSC score was constructed to quantify the stemness of individual tumors. Results: Three different cancer stem cells related subtypes were identified, which were related to different biological processes and clinical outcomes. And the three subtypes have different TME cells infiltrating characteristics. We constructed a scoring system called CSC score. Then we found that the prognosis of patients was predicted by CSC score, and patients with low CSC score had prolonged survival. Further analyses showed that low CSC score was correlated with enhanced immune infiltration. CSC score may predict the effect of immunotherapy, and patients with low CSC score may have better immune response and clinical prognosis. Conclusions: This work revealed that cancer stemness is significantly associated with TME complexity and diversity in osteosarcoma. CSC score could be used to assess the stemness of individual patients, improve our comprehension of TME characteristics, and direct more effective immune therapy.